Probing halogen–halogen interactions in solution. Issue 48 (29th November 2017) - Ayzac, V.; Raynal, M.; Isare, B.; Idé, J.; Brocorens, P.; Lazzaroni, R.; Etienne, T.; Monari, A.; Assfeld, X.; Bouteiller, L.
Abstract : Weak but measurable: a supramolecular balance detects interactions between CBr3 groups in solution and estimates the corresponding free energy (0.2 kJ mol −1 ). Abstract : Halogen–halogen interactions are a particularly interesting class of halogen bonds that are known to be essential design elements in crystal engineering. In solution, it is likely that halogen–halogen interactions also play a role, but the weakness of this interaction makes it difficult to characterize or even simply detect. We have designed a supramolecular balance that allows detecting Br⋯Br interactions between CBr3 groups in solution and close to room temperature. The sensitivity and versatility of the chosen platform have allowed accumulating consistent data. In halogenoalkane solvents, we propose estimates for the free energy of these weak halogen bond interactions. In toluene solutions, we show that the interactions between Br atoms and the solvent aromatic groups dominate over the Br⋯Br interactions.